Pneumonitis Akut dan Gagal Napas Setelah Mendapatkan Injeksi Silikon Cair di Payudara: [Acute Pneumonitis and Respiratory Failure after Breast Silicon Injection: A Case Report] - Cut Diana Laili; Daniel Maranatha (Jurnal Respirasi, 2015)
Background; Liquid silicone is a synthetic polymer incorporating oxygen and the semimetallic element silicon. It is widely  used in plastic and reconstructive surgery as it displays little change in physical characteristicswith temperature and age, is poorly  immunogenic, and is not carcinogenic. Case; We report a case of a 27-year-old woman presented to the hospital with the chief complain  progressive shortness of breath, pleuritic chest pain, productive cough, hemoptysis and fever after liquid silicone injections to the  mammae for cosmetic augmentation. Physical examination: tachycardia, tachypneu, hypertermia and diffuse rhonchi throughout the  lungs. Abnormalities laboratory tests gave leuchositosis, granulositosis, increasing trassaminase serum, D-dimer elevation, Arterial  blood gas analysis results respiratory disstres tipe 1. Chest radiograph showed difus bilateral infiltrates, CT angiography was negative  for an acute embolus but demonstrated infiltrates in superior lobus dextra, segment lateral lobus medius dan segment apicoposterior  Sinistra. Conclusion;  Patients with diagnosis of acut pneumonitis and respiratory disstres syndroma after liquid silicone injection to  the mammae, supportive therapy with O2 Ventilator and methylprednisolon low dose gives satisfactory result with radiological and  clinical.